2015
DOI: 10.1007/s12687-015-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in preferences for models of consent for biobanks between Black and White women

Abstract: Biobanks are essential resources, and participation by individuals from diverse groups is needed. Various models of consent have been proposed for secondary research use of biospecimens, differing in level of donor control and information received. Data are needed regarding participant preferences for models of consent, particularly among minorities. We conducted qualitative semi-structured interviews with 60 women to examine their attitudes about different models of consent. Recruitment was stratified by race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…We found that participants generally understood information on topics such as privacy and return of individual results. These topics were the subjects of the most common queries related to secondary research use of biospecimens found in our previous research[37]. We also found that topics such as possible risks of the use of biospecimens were least understood, which was similarly found in a prior study by Klima and colleagues[34].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We found that participants generally understood information on topics such as privacy and return of individual results. These topics were the subjects of the most common queries related to secondary research use of biospecimens found in our previous research[37]. We also found that topics such as possible risks of the use of biospecimens were least understood, which was similarly found in a prior study by Klima and colleagues[34].…”
Section: Discussionsupporting
confidence: 83%
“…We developed the content based on prior research by ourselves and others highlighting particularly difficult topics related to biobanks[33-35, 37] and integrated our prior findings about difficult terms in developing the wording of the text[37]. Each of the three brochures contained the following elements: Title page introducing the topic of the brochure; back page with information on the affiliated institution; a Frequently Asked Questions section; a graphic illustrating what happens when a sample is donated to a biobank (Figure 1); and sections describing the purpose of the research, the process of biospecimen donation, timing of consent process, and information about future research that might be conducted using stored biospecimens (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many key stakeholders commented on the Notice of Proposed Rule Making against obtaining consent due to the minimal risk nature of biospecimen research and the logistics of obtaining informed consent from populations within the context of clinical care and competing clinical needs (Health and Human Services 2015). Some published research with varied populations supports these comments, indicating that the public does not want to be refer each research project that uses their biospecimens (Simon et al 2011; Brown et al 2016; Garrison et al 2016). Yet, additional evidence supports a conclusion that the public wants to know about research with their biospecimens and more importantly, they want to be asked for their permission (Hendrix et al 2013; Javitt 2013; Botkin et al 2014, Hayeems et al 2016).…”
Section: Discussionmentioning
confidence: 99%